Nutritional strategies in an elite wheelchair marathoner at 3900 m altitude: a case report - Sanz-Quinto, S.; Moya-Ramón, M.; Brizuela, G.; Rice, I.; Urbán, T.; López-Grueso, R. (Journal of the International Society of Sports Nutrition, 2019)
Background: Altitude training is a common practice among middle-distance and marathon runners. During acclimatization, sympathetic drive may increase resting metabolic rate (RMR), therefore implementation of targeted nutritional interventions based on training demands and environmental conditions becomes paramount. This single case study represents the first nutritional intervention performed under hypobaric hypoxic conditions (3900 m) in Paralympic sport. These results may elucidate the unique nutritional requirements of upper body endurance athletes training at altitude. Case presentation: This case study examined the effects of a nutritional intervention on the body mass of a 36-year-old professional wheelchair athlete (silver medalist at the Paralympic Games and 106 victories in assorted road events) during a five-week altitude training camp, divided into pre-altitude at sea level (BN), acclimatization to altitude (Puno, 3860 m) (BH), specific training (W1,2,3,4) and return to sea level (Post) phases. Energy intake (kcal) and body mass (kg) were recorded daily. Results demonstrated significant decrease in body mass between BN and BH (52.6 ± 0.4 vs 50.7 ± 0.5 kg, P < 0.001) which returned to pre-altitude values, upon returning to sea level at Post (52.1 ± 0.5 kg). A greater daily intake was observed during BH (2899 ± 670 kcal) and W1,2,3 (3037 ± 490; 3116 ± 170; 3101 ± 385 kcal) compared to BN (2397 ± 242 kcal, P < 0.01) and Post (2411 ± 137 kcal, P < 0.01). No differences were reported between W4 (2786 ± 375?kcal), BN and Post. The amount of carbohydrates ingested (g · kg-1) was greater in W1,2,3, (9.6 ± 2.1; 9.9 ± 1.2; 9.6 ± 1.2) than in BN (7.1 ± 1.2) and Post (6.3 ± 0.8, P < 0.001). Effect sizes (Cohen`s d) for all variables relative to BN (all time points) exceed a large effect (d > 0.80). Conclusions: These results suggest an elite wheelchair marathoner training at 3860?m required increased nutrient requirements as well as the systematic control needed to re-adapt a nutritional program. Moreover, our findings highlight training and nutritional prescription optimization of elite wheelchair athletes, under challenging environmental conditions.